Comparative Efficacy of Pharmacological and Nonpharmacological Interventions for Acne Vulgaris: A Network Meta-Analysis - Shi, Qingyang; Tan, Lizi; Chen, Zhe; Ge, Long; Zhang, Xiaoyan; Yang, Fengwen; Liu, Chunxiang; Zhang, Junhua (Frontiers in Pharmacology, 2020)
Background: Acne has several effects on physical symptoms, but the main impacts are on the quality of life, which can be improved by treatment. There are many types of treatments for acne, but less evidence comparing to their relative efficacy. Objectives: To assess the comparative efficacy of pharmacological and non-pharmacological interventions for acne through a network meta-analysis. Methods: We searched PubMed, Embase and the Cochrane Central Register of Controlled Trials (CENTRAL) from inception to April 2019, to include randomized controlled trials (RCTs) for acne that compared topical antibiotics (TA), benzoyl peroxide (BPO), topical retinoids (TR), oral antibiotics (OA), lasers, light devices including LED device (LED), photodynamic therapy (PDT) and intense pulsed light, chemical peels (CP), miscellaneous therapies or complementary and alternative medicine (MTCAM) or their combinations. We performed Bayesian network meta-analysis with random effects for all treatments that were compared with placebo and each other. Mean differences (MD) of lesions count and risk ratio of adverse events with their 95% credible intervals were calculated, and all interventions were ranked by the Surface Under the Cumulative Ranking (SUCRA) values. Sensitivity analyses were carried out with different priors, and meta-regression was applied for nine effect modifiers. Results: Seventy-three RCTs (27745 patients with mild to moderate acne), comparing 30 grouped intervention categories, were included with low to moderate risk of bias. For adverse effects, OA had more risk in combination treatment with others. For non-inflammatory lesions, seventeen interventions had significant differences and three interventions (TR+BPO: -21.89[-28.97, -14.76]; TR+BPO+MTCAM: -22.48[-34.13, -10.70]; TA+BPO+CP: -20.63[-33.97, -7.13]) were superior to others with 94%, 94%, 91% SUCRA values, respectively. For inflammatory lesions, nineteen interventions were significantly better than placebo, and three interventions (TR+BPO: -12.13, 95%CrI[-18.41, -5.80]; TR+BPO+MTCAM: -13.21[-23.39, -3.04]; LED: -11.30[-18.34, -4.42]) were superior to others (SUCRA: 81%, 81%, 77%, respectively). Conclusions: Current evidence supports the suggestion that TR+BPO and TA+BPO are the best options for mild to moderate acne. LED is another option for inflammatory lesions when drug resistance occurs. All combinations involved with OA showed more risk of adverse events than others. However, the evidence of this study should be cautiously used due to the limitations.